Media Culture in Nomadic Communities. - Hahn, Allison (Amsterdam University Press, 2021)
Media Culture in Nomadic Communities examines the ways that new technologies and ICT infrastructures have changed the communicative norms and patterns that regulate mobile and nomadic communities' engagement in local and international deliberative decision making. Each chapter examines a unique communicative event, such has how the Maasai of Tanzania have used online petitions to demand government action. How Mongolians in northern China have used micro blogs to record and debate land tenure. And how herding communities from around the world have supported the Lakota Sioux protests at Standing Rock. Through these case studies, Hahn argues that mobile and nomadic communities are creating and utilizing new communicative networks that are radically changing local, national, and international deliberations. Bron: Flaptekst, uitgeversinformatie.